(untitled) (Indo-MathEdu Intellectuals Journal, 2025)
The habit of swearing and insulting can have a negative impact on students’ social and emotional development, thus affecting the learning atmosphere at school. This study aims to find out the habit of swearing and insulting in the SDN 3 Buntulia environment and make efforts to prevent it. This study uses a quantitative method by distributing questionnaires to students to collect data to analyze the frequency of these habits. The results of this study show that although most students know the meaning of swear words and many of them have heard their classmates, only a small percentage admit to using abusive words. This shows that awareness of the use of vulgar language is still low and the need to increase prevention in schools to limit such behavior. For further research, it is better to use a mixed method by adding interviews or group discussions to obtain results. Gain a deeper understanding of the reasoning behind abusive and offensive behavior in students.